Tradition as a condition of development (Móin-Móin - Revista de Estudios sobre Teatro de Formas Animadas, 2018)
The article reflects on tradition and contemporaneity in the philosophy of training of the puppeteer in Russian schools.Keywords: Pupperteer. Professional qualification. Tradition. Contemporaneity